Polaryzacja społecznych efektów reklam komercyjnych – analiza mechanizmów działania na przykładzie nastoletnich odbiorców - Maksymiuk, Renata Anna; Jasielska, Aleksandra (Wydawnictwo Naukowe UAM, 2014)
Adolescence is the period of important changes of the individual’s emotional, cognitive and social development. These changes occur in a specific social and cultural environment, of which advertising is part. Because young people are the target group of many products and commercials, it is worth highlighting the social role of advertising. Usually it is identified with negative consequences (like unhealthy habits). But some social effects of advertising may also be positive (e.g. dissemination of a healthy lifestyle). The article presents: 1) a pattern of social effects of advertising, 2) examples of polarization of the social effects of advertising, and 3) explanation of the mechanism of the opposite effects of advertisements.
Polarizations of the Social Effects of Advertising – Analysis of Impact on Adolescents
Keywords: social effects of advertising; polarization of effects of advertising; adolescence; consumer education